Darbininkų jaunimo lektūros tyrimų metodologiniai metodiniai ypatumai - Rimša, Vytautas (Knygotyra, 1986)
There is accumulated a certain amount of methodical, methodological and organisational experience in the field of research of workers' reading in Lithuanian SSR and in Soviet Union as a whole. Still, methodical and methodological problems of such research as separate object have been studied insufficiently.In our programme of joint republican centralised sociological and psychological research "Role of the Libraries in Development and Satisfaction of Professional and Spiritual Requests of Young Workers" these problems have been solved with regard of the shortcomings of all the previous specialised research. Characteristical methodical and methodological features of given programme are: elaboration of systematic complex conception of the cognition of young workers' educational and instructional processes; connection and strict subordination of general and special scientific methods; systematical approach to processes and phenomena of reading; direct use of the series of experiments in the course of research; solution of certain problems of methodics and methodology of the sociopsychological research.As specific features of this research may be considered the representability of the sampling of respondents and procedural bases with consideration of their parameters of various dimensions; also some peculiarities in the organisation of the research. Characteristic differences of general and special methods, as well as experience of previous researches, have been taken into account.The object of this search is the rise of the scientifical theoretical level of given research.